2020
DOI: 10.1371/journal.pone.0228332
|View full text |Cite
|
Sign up to set email alerts
|

Camelid husbandry in the Atacama Desert? A stable isotope study of camelid bone collagen and textiles from the Lluta and Camarones Valleys, northern Chile

Abstract: Management of camelids in the coastal valleys of the Andes has generated much debate in recent years. Zooarchaeological and isotopic studies have demonstrated that in the coastal valleys of northern and southern Peru there were locally maintained camelid herds. Because of the hyperarid conditions of the northern coast of Chile, this region has been assumed to be unsuitable for the raising of camelids. In this study we report stable carbon and nitrogen isotopic compositions of camelid bone collagen and textiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 129 publications
1
9
0
3
Order By: Relevance
“…Similar to modern studies, paleontological and archaeological studies have reported high dietary plasticity, in which populations oscillate between C 3 and C 4 feeders (MacFadden and Schockey 1997;Feranec 2003;Gil et al 2016;Yann et al 2016;González-Guarda et al 2017;Domingo et al 2020;Gayo et al 2020;Szpak and Valenzuela 2020). Given their opportunistic behavior, the feeding habits of southern Brazilian camelids may have been the result of forage availability, ecological opportunity, and intra-and interspecific competition, as discussed in the following paragraphs.…”
Section: Resultsmentioning
confidence: 66%
“…Similar to modern studies, paleontological and archaeological studies have reported high dietary plasticity, in which populations oscillate between C 3 and C 4 feeders (MacFadden and Schockey 1997;Feranec 2003;Gil et al 2016;Yann et al 2016;González-Guarda et al 2017;Domingo et al 2020;Gayo et al 2020;Szpak and Valenzuela 2020). Given their opportunistic behavior, the feeding habits of southern Brazilian camelids may have been the result of forage availability, ecological opportunity, and intra-and interspecific competition, as discussed in the following paragraphs.…”
Section: Resultsmentioning
confidence: 66%
“…Indeed, at lower elevation sites (800–1300 masl) with fossil or modern Prosopis forests (Guatacondo, Quillagua, San Salvador), macro or micro scale analyses of pellets reveal that camelids were ingesting pods as well as other local grazing plants. This environment is not ideal for camelid herding when compared to the puna’s rich, stable and productive grasslands and bofedales (Kuznar, 2001; Núñez, 2005; Núñez and Santoro, 1988; Rivera, 2005; Santoro et al, 2005; Szpak and Valenzuela, 2020). The breeding of camelids outside of this range might have been restricted to watered salares , oases, and riverine vegetation or irrigated areas, where crops such as maize or seasonal transhumance complemented natural restrictions (Dufour et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This encouragement probably also attracted wild fauna, reproducing hunting gathering strategies within the context of these new economies. Most of the ultimately stable isotopic studies carried out to gain insights into lowland husbandry have shown a diverse set of strategies to feed and maintain these herds (Gayo et al, 2020; Mader et al, 2018; Szpak and Valenzuela, 2020; Tomczyk et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Collagen quality was assessed using the following well-established criteria: C:N Atomic (2.9–3.6), %C (> 13.0%), and %N (> 4.5%) (Ambrose 1990 ; DeNiro 1985 ). Although quality control indicators for archeological keratin have not been established for hair and nail samples, we use the C:N Atomic range (3.0–3.8) observed for modern samples to assess keratin quality (Szpak and Valenzuela 2020 ).…”
Section: Methodsmentioning
confidence: 99%